Utility of [18F] Fluoro-Deoxyglucose Positron Emission Tomography/Computed Tomography for Staging and Therapy Response Evaluation in Pediatric Rhabdomyosarcoma: A Case Series and Literature Review - Sa, Ri; Liu, Danyan; Zhao, Hongguang; Hou, Sen; Lin, Qiuyu; Guan, Feng (Frontiers in Medicine, 2020)
Background: The role of [18F] fluoro-deoxyglucose [[18F] FDG] positron emission tomography (PET)/computed tomography (CT) in pediatric rhabdomyosarcoma (RMS) is not well-established. This manuscript explores the role of staging and therapy response evaluation of PET/CT in a series of patients with RMS. Methods: Thirteen consecutive patients with pathologically proven RMS underwent baseline PET/CT scan and a second PET/CT for evaluation of therapy response. Maximum standardized uptake value (SUVmax), mean standardized uptake value (SUVmean), highest standardized uptake peak value (SUVpeak), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) were obtained from baseline PET/CT and were used as potential predictors for evaluation of metabolic treatment response. Results: On baseline PET/CT, most RMSs are located in the pelvic cavity, and upper arms ranked second. The primary lesions were large and showed invasion to the surrounding tissues. Lymph node metastases were seen in eight patients, and eight patients showed distant metastasis to the lung, liver, and bone. The median SUVmax, SUVmean, and SUVpeak of primary sites were 7.1, 4.0, and 5.9, respectively. The median MTV and TLG were 196.6 cm3 and 780.2, respectively. After therapy, six patients received complete metabolic response (CMR) and non-CMR occurred in seven patients on the second PET/CT. SUVmax, SUVpeak, MTV, and TLG in patients with CMR were significantly lower than those in patients with non-CMR. Conclusions: Primary sites and metastatic lesions of RMS demonstrate increased glycolytic activity, which may allow them to be imaged using [18F] FDG PET/CT. Metabolic parameters derived from the baseline PET/CT have potential value for predicting CMR to therapy in pediatric RMS.